2008
DOI: 10.1291/hypres.31.1331
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction and Physical Disability Are Associated with Mortality in Extremely Elderly Patients

Abstract: A few reports have demonstrated that cognitive or physical dysfunction is associated with increased mortality in very elderly patients, those over 80 years of age. Using simple clinical tests, we evaluated the impact of cognitive or physical dysfunction on future total and cardiovascular deaths. We conducted a multicenter prospective study of 523 extremely elderly outpatients, aged ≥80 years (mean ± SD age: 84 ± 5.3 years). These patients had normal activities of daily living at baseline. They were followed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Our results of increased mortality for those with poor TUG performance correspond well with results from other similar studies [51, 52, 5558]. However, some of these studies did not include both genders [51, 52].…”
Section: Discussionsupporting
confidence: 91%
“…Our results of increased mortality for those with poor TUG performance correspond well with results from other similar studies [51, 52, 5558]. However, some of these studies did not include both genders [51, 52].…”
Section: Discussionsupporting
confidence: 91%
“… found a strong association in postmenopausal women and Hoshide et al . reported a correlation between TUG and cardiovascular mortality in the very old subjects at least 80 years of age. Lastly, according to Davis et al .…”
Section: Discussionmentioning
confidence: 95%
“…The simple visual WM test used in this study easily evaluated WM function even in elderly patients ≥80 years. As we also reported regarding this test (for which the association between the decrease in cognitive function and mortality was established), we observed that cognitive dysfunction assessed by this same simple visual WM test was an independent risk factor for total death and cardiovascular death in elderly ≥80 years, which indicates that this simple test would be an effective method for evaluating both the cognitive function and mortality risk in the very elderly. Further studies are needed to validate the clinical implication of this simple test.…”
Section: Discussionmentioning
confidence: 99%